Virus-specific Dicer-substrate siRNA swarms inhibit SARS-CoV-2 infection in TMPRSS2-expressing Vero E6 cells - Jiang, Miao; Laine, Larissa; Kolehmainen, Pekka; Kakkola, Laura; Avelin, Veera; Väisänen, Elina; Poranen, Minna M.; Österlund, Pamela; Julkunen, Ilkka (Frontiers in Microbiology, 2024)
After 4 years of the COVID-19 pandemic, SARS-CoV-2 continues to circulate with epidemic waves caused by evolving new variants. Although the rapid development of vaccines and approved antiviral drugs has reduced virus transmission and mitigated the symptoms of infection, the continuous emergence of new variants and the lack of simple-use (non-hospitalized, easy timing, local delivery, direct acting, and host-targeting) treatment modalities have limited the effectiveness of COVID-19 vaccines and drugs. Therefore, novel therapeutic approaches against SARS-CoV-2 infection are still urgently needed. As a positive-sense single-stranded RNA virus, SARS-CoV-2 is highly susceptible to RNA interference (RNAi). Accordingly, small interfering (si)RNAs targeting different regions of SARS-CoV-2 genome can effectively block the expression and replication of the virus. However, the rapid emergence of new SARS-CoV-2 variants with different genomic mutations has led to the problem of viral escape from the targets of RNAi strategy, which has increased the potential of off-target effects by siRNA and decreased the efficacy of long-term use of siRNA treatment. In our study, we enzymatically generated a set of Dicer-substrate (D)siRNA swarms containing DsiRNAs targeting single or multiple conserved sequences of SARS-CoV-2 genome by using in vitro transcription, replication and Dicer digestion system. Pre-transfection of these DsiRNA swarms into Vero E6-TMPRSS2 cells inhibited the replication of several SARS-CoV-2 variants, including the recent Omicron subvariants BQ.1.1 and XBB.1.5. This in vitro investigation of novel DsiRNA swarms provides solid evidence for the feasibility of this new RNAi strategy in the prevention and treatment of SARS-CoV-2 infection.